2020
DOI: 10.1007/s00395-020-0806-2
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Nucleotide-binding oligomerization domain-containing proteins (NOD) 1 and 2 reduces atherosclerosis

Abstract: Atherosclerosis is crucially fueled by inflammatory pathways including pattern recognition receptor (PRR)-related signaling of the innate immune system. Currently, the impact of the cytoplasmic PRRs nucleotide-binding oligomerization domaincontaining protein (NOD) 1 and 2 is incompletely characterized. We, therefore, generated Nod1/Nod2 double knockout mice on a low-density lipoprotein receptor (Ldlr)-deficient background (= Ldlr −/− Nod1/2 −/−) which were subsequently analyzed regarding experimental atheroscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…Therefore, our findings demonstrating a direct link between NOD1 and plaque vulnerability in Apoe −/− mice may be helpful to the clinical practice in terms of the events that precede plaque rupture during atherothrombosis, such as NC formation, the cell-death in the lesion area or the composition of the fibrotic tissue. Moreover, a recent work combining Nod1 and Nod2 deficiency under the Ldlr −/− background shows similar results to those reported in this work [ 28 ]; however, in our animal model, whereas NOD1 was highly upregulated under HFD regime, NOD2 levels remained unchanged ( Figure S9 ) stressing the relevance of NOD1 in the context of atherosclerosis.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, our findings demonstrating a direct link between NOD1 and plaque vulnerability in Apoe −/− mice may be helpful to the clinical practice in terms of the events that precede plaque rupture during atherothrombosis, such as NC formation, the cell-death in the lesion area or the composition of the fibrotic tissue. Moreover, a recent work combining Nod1 and Nod2 deficiency under the Ldlr −/− background shows similar results to those reported in this work [ 28 ]; however, in our animal model, whereas NOD1 was highly upregulated under HFD regime, NOD2 levels remained unchanged ( Figure S9 ) stressing the relevance of NOD1 in the context of atherosclerosis.…”
Section: Discussionsupporting
confidence: 90%
“…Under normoxic conditions, BCL2L1 binds to PGAM5 and inhibits its phosphatase activity, thus preventing FUNDC1 dephosphorylation and inhibiting mitophagy. However, following hypoxia or FCCP treatment, BCL2L1 is degraded, PGAM5 is activated, and FUNDC1 is dephosphorylated at Ser13, thus inducing mitophagy ( Ma et al, 2020a ; Vlacil et al, 2020 ). Loss- and gain-of-function assays indicated that the BCL2L1 level determines the extent of PGAM5-induced FUNDC1 dephosphorylation and mitophagy ( Ma et al, 2020a ).…”
Section: Receptor-dependent and Receptor-independent Pathwaysmentioning
confidence: 99%
“… 409 In addition to TLRs, the lack of NOD1 and NOD2 can lead to lipid deposition of atherosclerotic plaques and the reduction of inflammatory cell infiltration, so it has been identified as pre-disease factors. 410 …”
Section: Prr-related Diseasesmentioning
confidence: 99%